Pangenomic analysis of Coxiella burnetii unveils new traits in genome architecture - Abou Abdallah, Rita; Million, Matthieu; Delerce, Jeremy; Anani, Hussein; Diop, Awa; Caputo, Aurelia; Zgheib, Rita; Rousset, Elodie; Sidi Boumedine, Karim; Raoult, Didier; Fournier, Pierre-Edouard (Frontiers in Microbiology, 2022)
Coxiella burnetii is the etiological agent of Q fever, a worldwide zoonosis able to cause large outbreaks. The disease is polymorphic. Symptomatic primary infection is called acute Q fever and is associated with hepatitis, pneumonia, fever and auto-immune complications while persistent focalized infections, mainly endocarditis and vascular infections, occurred in a minority of patients but are potentially lethal. In order to evaluate the genetic diversity, evolution, as well as genetic determinants of antibiotic resistance, pathogenicity and ability to cause outbreaks of C. burnetii, we performed a pangenomic analysis of 75 strains including 63 newly sequenced genomes. Our analysis demonstrated that C. burnetii has an open pangenome with a high genomic plasticity, higher than that of other intracellular bacteria. The core- and pan-genomes are made of 1,211 and 4,501 genes, respectively (ratio 0.27). The core gene-based phylogenetic analysis matched that obtained from multi-spacer typing and the distribution of plasmid types. Some genotypes were associated to specific clinical forms and countries. A significant association was also found between clinical forms and plasmids. Strains with QpRS plasmid were never found in acute Q fever. In addition, the Guyanese strain CB175, the most virulent strain to date, exhibited a unique MST genotype, a distinct COG profile and an important variation in gene number that may explain its unique pathogenesis. Therefore, strain specific factors play an important role in determining the clinical manifestations of Q fever alongside with host-specific factors (valvular and vascular defects notably).